2010
DOI: 10.5012/bkcs.2010.31.04.929
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Constituents from Acer mandshuricum and Their Effects on the Function of Osteoblastic MC3T3-E1 Cells

Abstract: A new compound, 4-methoxyl 5-hydroxymethyl benzoic 3-O-β-D-glucopyranoside (1), has been isolated from the leaves and stems of Acer mandshuricum, along with nine known compounds (2-10). Their structures were determined by a variety of spectroscopic analyses. The effect of compounds 1-10 on the function of osteoblastic MC3T3-E1 cells was examined by determining alkaline phosphatase (ALP) activity, collagen synthesis, and mineralization. Compound 1 significantly increased the function of osteoblastic MC3T3-E1 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…PGG, which was previously isolated in our laboratory from winged sumac (Rhus copallinum) [37], showed the most potent antioxidant activity of 4.2 µM. Overall, as expected, the other classes of phenolics, including the flavonoids (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), and other phenolic derivatives (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37) also showed antioxidant activity with a broad range of IC 50 values ranging from 31.8 to 8311.5 µM. However, the sesquiterpenoids, 38 and 39, did not show any antioxidant effects in this assay.…”
supporting
confidence: 64%
“…PGG, which was previously isolated in our laboratory from winged sumac (Rhus copallinum) [37], showed the most potent antioxidant activity of 4.2 µM. Overall, as expected, the other classes of phenolics, including the flavonoids (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), and other phenolic derivatives (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37) also showed antioxidant activity with a broad range of IC 50 values ranging from 31.8 to 8311.5 µM. However, the sesquiterpenoids, 38 and 39, did not show any antioxidant effects in this assay.…”
supporting
confidence: 64%
“…The 13 C-NMR spectrum (DMSO- d 6 ) showed fifteen carbon signals, among which six are assigned to one sugar unit, nine to the aglycone moiety, and the nine aglycone moiety carbon signals were attributed to two methyl signals, two methine signals and five quaternary carbons by DEPT and HMQC spectra. By analyzing the 1 H-and 13 C-NMR data along with the reported data [ 11 ], the aglycone moiety was identified as the derivative of gallic acid. The correlations of one methyl protons at δ 3.77 to C-3 at δ 153.0 and another methyl protons at δ 3.79 to C-7 at δ 166.2 in the HMBC spectrum indicated that one methyl group is connected to C-3 through oxygen and another methyl group to C-7 through oxygen.…”
Section: Resultsmentioning
confidence: 99%
“…The structure elucidation of the compounds was performed based on 2D NMR and HR-MS analyses. They were identified as gallic acid (2) (3) (Choi et al, 2013), 4-methoxyl-5-hydroxymethyl 3-O-β-Dglucopyranoside benzoic acid (5) (Ding et al, 2010), 3,5dihydroxy-4-methoxy benzoic acid methyl ester (6) (Arisawa et al, 1991), and eriodictyol 7-O-methylether 3′-O-β-Dglucopyranoside (7) (Wada et al, 1986) (Fig. 1).…”
Section: Isolation Of the Active Compounds From The Methanolic Extracmentioning
confidence: 99%